PENGELOLAAN KELAS INDUSTRI DI SEKOLAH MENENGAH KEJURUAN - Priambudi, Puguh; Mahmudah, Fitri Nur; Susatya, Edhy (Universitas Negeri Padang, 2020)
This study aims to describe the management of industrial classes in SMK Muhammadiyah 2 Ajibarang. This research uses a qualitative type with a case study approach. Research subjects were the deputy head of public relations, the deputy head of the curriculum, the head of the engineering engineering program, the head of the light vehicle engineering program and the head of the motorcycle engineering expertise program. Place of research at SMK Muhammadiyah 2 Ajibarang. Data collection techniques using interviews, observation, and documentation. The collected data were analyzed with the model of Miles, Hubermen, and Saldana. Research data 1) Industrial class planning includes aspects of students carried out by industry and schools as the organizer. The human resource aspect is carried out by means of instructor training organized by industry to increase knowledge about the industry. The curriculum aspect is carried out by synchronizing the school curriculum with the industrial curriculum, then the aspect of infrastructure facilities is carried out by industry and schools with industrial involvement in the form of setting industry class standards and procuring infrastructure and forms of school involvement in the form of procurement. 2) The implementation of industrial classes includes learning that is adjusted to the established curriculum and the internship carried out in the industry. 3) evaluation which includes evaluating student learning outcomes, in the form of students getting certificates from the industry and evaluating the implementation of industrial classes in the form of internal meetings and visits made by schools to industry and industry to schools